New insights into Sirt1: potential therapeutic targets for the treatment of cerebral ischemic stroke - Tang, Hao; Wen, Jun; Qin, Ting; Chen, Yue; Huang, Jiagui; Yang, Qinghuan; Jiang, Peiran; Wang, Ling; Zhao, Yong; Yang, Qin (Frontiers in Cellular Neuroscience, 2023)
Ischemic stroke is one of the main causes of mortality and disability worldwide.However, the majority of patients are currently unable to benefit from intravenous thrombolysis or intravascular mechanical thrombectomy due to the limited treatment windows and serious complications. Silent mating type information regulation 2 homolog 1 (Sirt1), a nicotine adenine dinucleotide-dependent enzyme, has emerged as a potential therapeutic target for ischemic stroke due to its ability to maintain brain homeostasis and possess neuroprotective properties in a variety of pathological conditions for the central nervous system. Animal and clinical studies have shown that activation of Sirt1 can lessen neurological deficits and reduce the infarcted volume, offering promise for the treatment of ischemic stroke. In this review, we summarized the direct evidence and related mechanisms of Sirt1 providing neuroprotection against cerebral ischemic stroke. Firstly, we introduced the protein structure, catalytic mechanism and specific location of Sirt1 in the central nervous system. Secondly, we list the activators and inhibitors of Sirt1, which are primarily divided into three categories: natural, synthetic and physiological. Finally, we reviewed the neuroprotective effects of Sirt1 in ischemic stroke and discussed the specific mechanisms, including reducing neurological deficits by inhibiting various programmed cell death such as pyroptosis, necroptosis, ferroptosis and cuproptosis in the acute phase, as well as enhancing neurological repair by promoting angiogenesis and neurogenesis in the later stage. Our review aims to contribute to a deeper understanding of the critical role of Sirt1 in cerebral ischemic stroke and to offer novel therapeutic strategies for this condition.